Increase in leg stiffness reduces joint work during backpack carriage running at slow velocities - Liew, B.; Netto, Kevin; Morris, Susan (Human Kinetics, 2017)
© 2017 Human Kinetics, Inc. Optimal tuning of leg stiffness has been associated with better running economy. Running with a load is energetically expensive, which could have a significant impact on athletic performance where backpack carriage is involved. The purpose of this study was to investigate the impact of load magnitude and velocity on leg stiffness. We also explored the relationship between leg stiffness and running joint work. Thirty-one healthy participants ran overground at 3 velocities (3.0, 4.0, 5.0 m·s -1 ), whilst carrying 3 load magnitudes (0%, 10%, 20% weight). Leg stiffness was derived using the direct kinetic-kinematic method. Joint work data was previously reported in a separate study. Linear models were used to establish relationships between leg stiffness and load magnitude, velocity, and joint work. Our results found that leg stiffness did not increase with load magnitude. Increased leg stiffness was associated with reduced total joint work at 3.0 m·s -1 , but not at faster velocities. The association between leg stiffness and joint work at slower velocities could be due to an optimal covariation between skeletal and muscular components of leg stiffness, and limb attack angle. When running at a relatively comfortable velocity, greater leg stiffness may reflect a more energy efficient running pattern.